Rethinking Competence: A Nexus of Educational Models in the Context of Lifelong Learning - Dalia Bajis; Betty Chaar; Rebekah Moles (Pharmacy, 2020)
Competency-based education (CBE) “derives a curriculum from an analysis of a prospective or actual role in modern society and attempts to certify students’ progress on the basis of demonstrated performance in some or all aspects of that role”. This paper summarizes pertinent aspects of existing CBE models in health professions education; pharmacy education presented as an example. It presents a synthesis of these models to propose a new diagrammatic representation. A conceptual model for competency-based health professions education with a focus on learning and assessment is discussed. It is argued that various elements of CBE converge to holistically portray competency-based learning and assessment as essential in initial education and relevant to practitioners’ continuing professional development, especially in the context and importance of pursing lifelong learning practices.